Organoids – New Models for Host–Helminth Interactions. Issue 2 (February 2020) - Duque-Correa, María A.; Maizels, Rick M.; Grencis, Richard K.; Berriman, Matthew
Abstract : Organoids are multicellular culture systems that replicate tissue architecture and function, and are increasingly used as models of viral, bacterial, and protozoan infections. Organoids have great potential to improve our current understanding of helminth interactions with their hosts and to replace or reduce the dependence on using animal models. In this review, we discuss the applicability of this technology to helminth infection research, including strategies of co-culture of helminths or their products with organoids and the challenges, advantages, and drawbacks of the use of organoids for these studies. We also explore how complementing organoid systems with other cell types and components may allow more complex models to be generated in the future to further investigate helminth–host interactions. Highlights: Organoids are multicellular in vitro culture systems that closely resemble the architecture and function of the tissue of origin. Organoids are currently used to study host cell interactions with microorganisms, including viruses, bacteria, and parasites. Helminth research is lacking models that better recapitulate the interaction of the human/livestock host and parasites. Organoid cultures are of great potential to study helminth infections while their application in this field is in its infancy. The different components of the host–helminth in vivo interaction, including tissue architecture, polarization, and multicellularity, environmental cues, and biomechanical forces, should be considered when using organoids to recreate these parasitic infections. In the future, more complex systems integrating stromal and immune cells and microengineering technologies with organoid cultures will further empower the use of this system in helminth research.